A basic introduction to finite element methods for solving electrical problems - (:unkn) unknown (SILA SCIENCE, 2011)
This paper presents a tutorial introduction for an absolute beginner in 1-dimensional (1D) finite element method (FEM) analysis. The techniques of FEM is shown and visualized with examples, such as electrostatic, temperature and electric circuit problems of vital importance for electrical education students studying for a bachelor degree. Suggestions are offered on how the basic concepts can be developed and the extension to 2-dimensional (2D) finite element analysis is discussed. A step-by-step numerical procedure for coding is presented with suitable Mathematica programs that are ready to run. In this way, students can easily solve complex algorithms of Finite Element Methods.
Keywords: Finite element method; Electric education; Thermal and electrostatic devices; Mathematica